Analisis Semiotika Pierce pada Pertunjukan Tari Dhânggâ Madura - Ulfa Sufiya Rahmah; Sujinah Sujinah; Ali Nuke Affandy (Institut Teknologi Sepuluh Nopember, 2020)
Dhengge dance embodies the description of fishermen's activities that have a sense of beauty that is caused by movement and music produced by the mouth. Human life cannot be separated from signs, and signs always have a load of meaning. The symbols contained in this dance were analyzed qualitatively by Pierce's semiotics. The costumes of the dancers are interpreted by the fishermen as having a firm attitude and a fighting spirit in facing life, steadfast and tough. Freedom, openness, simplicity, courage, manliness, and persistence are among the cultural ethos of the Madurese people. The dance movement depicts a trip to go to sea, search for fish to return to the beach, which means that life can be likened to running a boat into the middle of the ocean which at times is hit by big waves and strong winds, the boat to lose control, lose direction and even sink. For that we need planning, hard work, togetherness, a sense of brotherhood and require patience, confidence, persistence, and surrender